Integration of Risk Accounting and Cost Management for Financial Sustainability in the Education Sector - Basrowi; Kusuma, Bayyu Indra; Suseno, Bambang Dwi; Afiah, Efi Tajuroh (Southeast Asian Journal of Science and Technology, 2025)
This study aims to analyze the integration of risk accounting and cost management in strengthening financial sustainability within educational sector institutions. The increasing financial uncertainty in education, combined with limited resources and rising operational costs, requires a more structured financial management approach that incorporates both risk awareness and cost efficiency. Risk accounting provides a framework for identifying and evaluating financial uncertainties, while cost management focuses on optimizing resource allocation and controlling expenditures to improve institutional performance. This research employs a qualitative approach using a literature-based analysis method. Data were collected from international journals, academic books, and institutional reports published between 2020 and 2026. The analysis was conducted through thematic interpretation to identify key patterns related to risk-based financial governance and cost efficiency in education sector institutions. The study emphasizes how the integration of these two approaches contributes to improving financial planning, accountability, and decision-making processes. The findings indicate that the integration of risk accounting and cost management enhances financial sustainability by enabling educational institutions to anticipate financial risks, improve budgeting accuracy, and reduce inefficiencies in resource utilization. Furthermore, this integration strengthens institutional governance by promoting transparency and accountability in financial reporting. However, challenges such as limited technical capacity, lack of standardized frameworks, and weak financial data integration remain significant barriers to effective implementation. The study concludes that the integration of risk accounting and cost management is essential for improving financial resilience and operational efficiency in education sector institutions. It recommends strengthening institutional capacity, developing standardized risk-based financial frameworks, and enhancing digital financial systems to support sustainable education financing.